Motorsport Valley revisited: Cluster evolution, strategic cluster coupling and resilience. (October 2021) - Henry, Nick; Angus, Tim; Jenkins, Mark
Over 20 years ago a series of papers identified a strikingly dominant economic cluster – the UK's Motorsport Valley (MSV) – which led to MSV becoming an international exemplar of concepts such as agglomeration, clusters and knowledge-driven systems of regional development. Utilising an evolutionary perspective on cluster development, this paper asks 'whatever happened to MSV?'. Drawing on the framework of strategic cluster coupling, four cluster development episodes are conceptualised that each depict the dynamic evolution of the cluster's multi-scalar institutional environment, strategic coupling trajectories and economic development outcomes. Reflecting the emerging synthesis between evolutionary economic geography and geographical political economy, the paper describes an extended case study of cluster development, an evolutionary process of strategic cluster coupling and, ultimately, an example of cluster resilience. Through a focus on strategic cluster coupling, the paper provides further understanding of cluster evolution and path development mechanisms at key moments of cluster reconfiguration – and an empirical update and continuation of the economic story and cluster lifecycle of MSV.